Evaluation of the functional activity of CD39 ectonucleotidase in regulatory T cells in children with inflammatory bowel diseases - T. V. Radygina; E. G. Sorokina; S. V. Petrichuk; D. G. Kuptsova; O. V. Kurbatova; A. S. Potapov; S. A. Afanasyeva (Медицинская иммунология)
In connection with the increasing incidence and prevalence of inflammatory bowel disease (IBD), the search for prognostic markers of the effectiveness of therapy is an urgent problem. An imbalance between Th17 lymphocytes and regulatory T cells (Treg) is a major defect in the immune system leading to IBD. Extracellular ATP produced during tissue damage, rebound pro-inflammatory effects, and activates Th17 cell differentiation. Ectonucleotidase CD39 catalyzes the dephosphorylation of ATP to AMP, followed by conversion to adenosine by CD73. CD39 is expressed in various cell types, including Treg. Aim – evaluate the functional activity of CD39+ in Treg in children with IBD using the luciferin-luciferase method.68 children with IBD were examined. Of these, 28 children were in remission, 40 were in exacerbation. The number of Tregs (CD4+CD25highCD127low) expressing CD39 was estimated by flow cytometry. The ATP concentration in supernatants and cells was determined using the luciferin-luciferase test. Results are presented as median (Me) and quartiles (Q0.25-Q0.75). The significance of differences between groups was assessed using the nonparametric Mann–Whitney U test.The relative number of CD39+Treg in patients in remission of IBD was significantly higher than in patients in a state of exacerbation. A decrease in ATP concentration under the influence of CD39+Treg in patients with IBD occurred immediately upon the addition of exogenous ATP. ATP in patients in remission decreased by 44.5% (Me 54.5 (41.5-65.9)), in patients in exacerbation – by 32.5% (Me 67.5 (59.7-71.3)). At the same time, in patients in remission, the decrease in the ATP content after 5 minutes of the reaction was significantly higher than in patients in the state of exacerbation (p = 0.01), after 30 minutes of the reaction, no significant difference was found. It was shown that samples with a smaller number of cells and a lower intensity of CD39 expression in Treg had a higher activity of CD39 ectonucleotidase.For efficient ATP hydrolysis, in addition to the amount of CD39 in Treg, their functional activity is important. The assessment of the catalytic activity of CD39 in Treg in patients with IBD is most informative in the first minutes after the addition of exogenous ATP. In patients in remission, the catalytic activity of CD39 in Treg was higher than in patients in a state of exacerbation.